PENERAPAN METODE COVID UNTUK MENINGKATKAN KOMPETENSI GURU DALAM PELAKSANAAN PEMBELAJARAN DI MASA COVID-19 - YR, Suyanti (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2022)
Teachers’ competency of SMP Negeri 5 Jujuhan in doing learning from home along Covid-19 Pandemy are still dissapointed. Of course, It influenced to the students’ ability. So, this research is meant to explain the applying of Conditioning, Organizing, Viewing, Interpreting, Deciding (covid) method in improving the teachers’ competency. This is School Action Research because all the teachers of SMP Negeri 5 Jujuhan roled as the research’s subject. The research was designed in two cycles. Each of them has the same phases : planning, doing, observing and reflecting. It used observation sheets and field note as the instrumen in collecting data. The results of the study show that (1) the principal must continue to provide a forum for developing teacher competence in order to maximize student competence. (2) The application of the COVID method is able to improve teacher competence in carrying out quality learning. (3) The application of the COVID method not only improves the professional competence of teachers but also improves motivation and learning behavior.